2017
DOI: 10.1161/jaha.117.006402
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Size and Long‐Term Risk of Recurrent Stroke After Acute Ischemic Stroke in Patients With Nonvalvular Atrial Fibrillation

Abstract: BackgroundAmong patients with ischemic stroke and atrial fibrillation, which ones are at high risk of recurrent stroke is unclear. This study aimed to determine whether left atrial size was associated with long‐term risk of stroke recurrence in patients with nonvalvular atrial fibrillation.Methods and ResultsIn this multicenter prospective cohort study, nonvalvular atrial fibrillation patients hospitalized for acute ischemic stroke were enrolled and followed up after discharge. Indexed‐left atrial diameter was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 56 publications
0
32
1
2
Order By: Relevance
“…Despite advancements in medical therapy, the risk of recurrent ischemic stroke treated with optimal medication therapy remains between 6.5% and 20% per year in Asia. [18][19][20][21] The incidence rate per 100 person-years of recurrent stroke in our study (0.543) was lower than that reported by Ogata and Omori (6.486 and 10.672, respectively).…”
Section: Recurrence Stroke After Ablation In Patients With Prior Stcontrasting
confidence: 77%
“…Despite advancements in medical therapy, the risk of recurrent ischemic stroke treated with optimal medication therapy remains between 6.5% and 20% per year in Asia. [18][19][20][21] The incidence rate per 100 person-years of recurrent stroke in our study (0.543) was lower than that reported by Ogata and Omori (6.486 and 10.672, respectively).…”
Section: Recurrence Stroke After Ablation In Patients With Prior Stcontrasting
confidence: 77%
“…A study by Shimizu et al (7) determined a positive correlation between LVD dysfunction and cerebral white matter lesions in elderly patients. A multicenter prospective cohort study indicated that the left atrial diameter index was significantly associated with the risk of stroke recurrence (8). Youth hypertension is defined as hypertension occurring in patients aged between 18 and 45 years.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that LA structural remodeling is a predictor of a series of clinical events or unfavorable outcomes, such as new‐onset heart failure, worsening of pre‐existing heart failure, recurrent stroke, and increased incidence of cardiovascular and all‐cause death . Since LA structural remodeling portends a negative effect, continuous efforts are made to slow down the progression of this process, even to reverse this process, termed as LA structural reverse remodeling.…”
Section: Introductionmentioning
confidence: 99%